(untitled) (International journal of artificial intelligence, 2025)
This article discusses the content, purpose and methodological foundations of the development of cognitive interests of primary school students in extracurricular activities and the organization of extracurricular activities with students. The role of extracurricular activities in the development of cognitive interest, creative activity and independent thinking in students is analyzed. The article describes the types, forms and stages of effective organization of extracurricular activities on a scientific basis.